'Twas the night before Christmas in New Mexico - Parry, Jo; Moore, Clement Clarke, 1779-1863. (Naperville, Illinois Hometown World, an imprint of Sourcebooks Kids, 2021)
Far, far away at the North Pole, Santa is busy planning his Christmas Eve journey across his favorite place -- New Mexico. Are you ready for Santa to visit your home? --page [4] of cover.
113578
Keywords: Santa Claus -- (Fictitious character) -- Juvenile fiction; Christmas stories; New Mexico -- Juvenile fiction; Christmas fiction; Fiction; Juvenile works; Picture books; Stories in rhyme